Prolonged Continuous Theta Burst Stimulation With Transcranial Magnetic Stimulation Analgesic Effects and Corticospinal Excitability in Chronic Neuropathic Pain: A Randomized Clinical Trial - Ying Liu; Xianwei Che; Junfeng Sun; Jiajun Chen; Bolin Tan; Weidong Qiu; Jinxuan Ren; Zhimin Huang; Lina Yu; Fengjiang Zhang; Jie Li; Bernadette M. Fitzgibbon; et al. (Anesthesia & Analgesia, 2026)
BACKGROUND: Repetitive transcranial magnetic stimulation (rTMS) may have an analgesic effect in neuropathic pain. However, clinical application is notably limited by a variable rate of responders. We aimed to (i) assess the analgesic efficacy of prolonged continuous theta burst stimulation (pcTBS) delivered to M1, (ii) study the analgesic effect of maintenance treatment in responders., and (iii) examine the analgesic efficacy of switching to the left dorsolateral prefrontal cortex (DLPFC) in nonresponders. METHODS: We conducted a randomized, sham-controlled, and double-blind study in chronic neuropathic pain participants (n = 94). In part 1, participants were randomized to receive 5 days of either pcTBS, 10-Hz rTMS, or sham stimulation over the left M1. In the subsequent parts, responders to either active treatment in part 1 continued with biweekly sessions for four weeks (part 2), while nonresponders in part 1 received 5 days of stimulation on the left DLPFC (part 3). Corticospinal excitability was assessed via measurements of motor-evoked potential (MEP) and cortical silent period (CSP) recorded from the right first dorsal interosseous (FDI) muscle. RESULTS: Among the 94 participants randomized into treatment groups, 5 days of M1 stimulation with either pcTBS or 10-Hz rTMS showed significant analgesia compared to baseline (mean [standard deviation SD]: 10-Hz 37.9 ± 17.5 vs 48.5 ± 16.0, P < .001; pcTBS 35.1 ± 15.3 vs 47.1 ± 15.1, P < .001), but the two active groups did not differ from each other ( P = .16). However, pcTBS induced more rapid corticospinal excitability changes (MEP pcTBS versus Sham: 188.5 ± 39.8 vs 102.2 ± 6.9, P = .044; CSP pcTBS versus Sham: 113.9 ± 3.8 vs 101.7 ± 3.3, P = .039), whereas no significant changes were observed in the 10-Hz group during the same period (MEP 10-Hz versus Sham:115.7 ± 9.3 vs 102.2 ± 6.9, P corrected = 1.000; CSP 10-Hz versus Sham: 103.6 ± 2.9 vs 101.7 ± 3.3, P corrected = 1.000). In the responder group, additional maintenance sessions further increased analgesia (time effect: Post2 versus Post1: 21.3 ± 2.1 vs 27.1 ± 2.3, P = .006) and maintained analgesic effect for 1 month in both the pcTBS and 10-Hz rTMS treatment groups (follow-up versus Post1: 29.9 ± 2.7 vs 27.1 ± 2.3, P = .74). Additional sessions also increased corticospinal excitability, and this was associated with less pain during the follow-up period ( r = −0.48, P = .037). Pain symptoms were improved more by pcTBS (post versus pre: 11.3 ± 5.5 vs 13.1 ± 5.3, P = .020) than by 10-Hz rTMS (post versus pre: 15.9 ± 7.2 vs 15.5 ± 6.4, P = .978) when both were applied to the left DLPFC in initial nonresponders. CONCLUSIONS: This study demonstrates that pcTBS applied to M1 is an effective treatment for chronic neuropathic pain, with analgesic efficacy comparable to conventional 10-Hz rTMS. The protocol offers a substantial reduction in treatment time, opening perspectives for more efficient clinical application.